On the Indentation of a Membrane Reinforced Elastic Halfspace: Analytical and Computational Approaches - Selvadurai, A.P.S.; Willner, Kai; Gaul, L. (Computational Methods in Contact Mechanics V, 2001)
This paper examines the problem of the surface indentation of an isotropic elastic halfspace, which is reinforced by an inextensible membrane and subjected to indentation by a rigid circular punch with a smooth flat base. The inextensibility constraint is assumed to be applicable over the entire region of the membrane of infinite extent, which is located at a finite depth below the surface of the elastic halfspace. The paper presents the formal results that can be recovered as limiting cases of the analytical formulation and compares these with results obtained via a finite element modelling of the problem, which also accommodates for the elasticity of the membrane.
UnivIS-Import:2015-04-16:Pub.2001.tech.FT.FT-TM.onthei